Women in Democracy: The political participation of women - Akhlaq Ahmad; Qaisar Khalid Mahmood; Muhammad Saud; Siti Mas'udah (Faculty of Social and Political Science, Universitas Airlangga, 2019)
Political participation of women has improved significantly in many western democracy settings; in Asian countries however, women are still left behind in terms of political participation. This article explores political participation of women in a gender-segregated society where women have disproportionate social status in a strongly patriarchal culture and political system. Femininity, political socialization, political interest, political efficacy, and patriarchal political culture were taken as predictors to assess the political participation of women. Structured interview schedules were administrated to 414 women voters from two randomly selected Tehsils, i.e. Jhang and Gujar Khan, of the Punjab Province in Pakistan. Data from the interviews were processed using Stepwise Multiple Linear Regression. The results revealed that predictors explained 58.3% of the variance in the political participation of women voters in Punjab. However, two constructs of femininity: morality and loyalty were not loaded in the model. The dominant, socially designed attributes that women should possess in Pakistani society are childbearing and rearing, love and care for parents/husband, homemaking, submissiveness, passivity, and dependence. The home/private sphere becomes the ideal, normative space for women to operate. On the other hand, men are characterized by decision making, production, independence, assertiveness, violence, and wider interaction. Thus, men are associated with the public and the public sphere. These feminine & masculine ideals are the basis of social practices and social relations in Pakistani society. These are internalized, taken for granted, and embedded into the culture, social structure, and social organization of Pakistani society.